2011
DOI: 10.1021/ml200010k
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ligand Binding and Efficiency

Abstract: b S Supporting Information T he primary goal of any drug discovery effort is to increase the potency of prospective compounds to the greatest degree possible while also optimizing the many other physical properties necessary for drug development. In most cases, little effort is invested in understanding the underlying thermodynamic quantities of enthalpy and entropy that are responsible for determining free energy. More recently, it has become common to recast binding free energies in terms of ligand efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
158
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 23 publications
5
158
0
1
Order By: Relevance
“…Analysis of experimental ITC data 33,41 across a wide range of chemotypes shows that the average entropy efficiency is little changed with size (supplementary Figure S1), but narrows in moving from small to large ligands. 42 By contrast, the enthalpy efficiencies show a much more dramatic trend with increasing size, which is similar to the trend seen with the overall LE values (ie derived from G). Very favorable enthalpy efficiencies are common for small ligands, but the average, and most favorable, enthalpy efficiencies for larger ligands are systematically reduced (see supplementary Figure S1).…”
Section: Binding Thermodynamics and Ligand Efficiencysupporting
confidence: 77%
See 2 more Smart Citations
“…Analysis of experimental ITC data 33,41 across a wide range of chemotypes shows that the average entropy efficiency is little changed with size (supplementary Figure S1), but narrows in moving from small to large ligands. 42 By contrast, the enthalpy efficiencies show a much more dramatic trend with increasing size, which is similar to the trend seen with the overall LE values (ie derived from G). Very favorable enthalpy efficiencies are common for small ligands, but the average, and most favorable, enthalpy efficiencies for larger ligands are systematically reduced (see supplementary Figure S1).…”
Section: Binding Thermodynamics and Ligand Efficiencysupporting
confidence: 77%
“…This was demonstrated with simple model systems 39 and is further supported by subsequent analysis of enthalpy and entropy efficiencies 42 showing that the size dependency is related to enthalpy (see Supplementary Figure S1). …”
Section: Box 2-size Independent Measures Of Ligand Efficiencymentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, information on changes in entropy and enthalpy can usefully guide the design of improved drug molecules (1), with advantageous specificity (2) and physical properties (3). However, calorimetric studies of biomolecular binding and folding often reveal unexpected changes in entropy and enthalpy that are difficult to interpret in terms of physical driving forces (4)(5)(6)(7)(8). Some of these puzzling results are instances of entropy-enthalpy compensation (9), a common but not universal (10,11) phenomenon in which perturbations of a system that increase the enthalpy also increase the entropy or vice versa; therefore, the net change in the free energy remains small.…”
mentioning
confidence: 99%
“…82 The authors found a good correlation between experimental binding affinities and the calculated binding free energies, leading them to speculate that the predicted binding sites were a good model to explain the experimental findings, though it is known that enthalpic factors alone do not necessarily produce accurate binding energies in docking studies. 86 In the final example of docking small molecules to Aβ fibrils, Keshet et al docked a small library of structurally distinct molecules to 20 different Aβ 40 fibril models. The authors concluded that Congo Red (a dye molecule), myricetin (a flavonoid), and melatonin (a neurotransmitter) shared common binding sites on the fibril.…”
mentioning
confidence: 99%